+0  
 
0
132
1
avatar

x^(2) - 6x = 1/2x + 42

Find x

Guest Aug 16, 2017
Sort: 

1+0 Answers

 #1
avatar+302 
0

For this, we need to transorm the eq. to standard form:

\(x^2-6x=\frac{1}{2}x+42\)

\(x^2-\frac{13}{2}x-42=0\)

Now to use the quadratic formula:

\(a=1\)

\(b=-\frac{13}{2}\)

\(c=-42\)

\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)

\(x = {-(-\frac{13}{2}) \pm \sqrt{(\frac{13}{2})^2-4(1)(-42)} \over 2(1)}\)

\(x = \frac{\frac{13}{2} \pm \sqrt{210+{1 \over 4}}}{2}\)

\(x = {{13 \over 2}\pm(14+{1 \over 2})\over 2}\)

\(x = {10+{1\over2}, -4}\)

 

laugh

Mathhemathh  Aug 16, 2017

27 Online Users

avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details